2001
DOI: 10.1038/labinvest.3780265
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Growth Regulatory Genes in Intraductal Breast Cancer Is Associated with Higher Nuclear Grade but Not with the Progression to Invasiveness

Abstract: Ductal carcinoma in situ (DCIS), as an identifiable progenitor lesion of invasive breast cancer, represents a morphologically, biologically, and prognostically heterogeneous disease. It is not clear which molecular mechanisms are involved in progression to infiltrative growth. In this study, 83 DCIS classified according to the Van Nuys grading scheme were examined for amplification of growth regulatory genes that have been found to be amplified in invasive breast cancer (c-erbB2, topoisomerase IIalpha, c-myc, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…The higher MNA, therefore, can be expected to reflect the increased proliferation in Nigerian breast cancer. This view is further substantiated by the study of Glöckner (2001) who showed that the amplification and increased expression of erbB2 (growth factor receptor associated with increased growth rate) is associated with higher nuclear grade in intraductal cancers.…”
Section: Discussionmentioning
confidence: 57%
“…The higher MNA, therefore, can be expected to reflect the increased proliferation in Nigerian breast cancer. This view is further substantiated by the study of Glöckner (2001) who showed that the amplification and increased expression of erbB2 (growth factor receptor associated with increased growth rate) is associated with higher nuclear grade in intraductal cancers.…”
Section: Discussionmentioning
confidence: 57%
“…PEG10 is activated in subsets of human breast and prostate carcinomas. A substantial subset of human breast carcinomas, including ductal carcinoma in situ, overexpress MYC either due to gene amplification or transcriptional deregulation (18)(19)(20). To ask whether the PEG10 gene is activated in primary human breast cancers, we carried out immunohistochemistry for PEG10 protein, using an affinity-purified polyclonal antiserum raised against a peptide epitope in the PEG10 major open reading frame (the RF1 protein isoform), in a series of 23 paraffin-embedded breast biopsies with standard histologic sections and in a second series of 161 breast cancer cases in a tissue array.…”
Section: Resultsmentioning
confidence: 99%
“…Even in studies in which amplification was detected in DCIS, the percentage of positive samples was low. For example, when Myc amplification was scored by using PCR analysis, only 6% (5/78) 69 or 7% (3/41) 38 of the DCIS samples were found to be positive. In the latter case, 27% (11/41) of the DCIS samples overexpressed Myc detected by IHC.…”
Section: Myc In Normal Human Breast and Breast Cancermentioning
confidence: 99%